(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background:Breast cancer (BC) is the second most common type of cancer and accounts for one-fourth of cases of all kinds of cancers among females. According to the World Health Organization (WHO), BC is the world's most prevalent type of cancer and is responsible for substantial numbers of disability-adjusted life years (DALYs) in women. BC affects all age groups and the incidences show an increasing trend after puberty and with increased age. The mortality rates associated with BC can be considerably minimized with the initiation of treatment at the early stages of the disease. However, due to the lack of awareness of BC and its early symptoms along with the stigma associated with cancers, especially in the rural population, many cases remain undiagnosed. Therefore, this study was carried out to assess the knowledge and awareness of BC among females residing in the rural parts of IndiaMethods:This was a prospective cross-sectional study that included 100 young female patients attending the outpatient department of Mahavir Institute of Medical Sciences (MIMS), Vikarabad, Telangana, India. Convenience sampling was applied and informed consent was obtained from all participants. A validated questionnaire was used to obtain data from the study subjects. The questionnaire had three parts that included sociodemographic characteristics, knowledge of BC, and the assessment based on the Champion's Health Belief Model Scale (CHBMS). The data collected were entered into Microsoft Excel sheets and were used to prepare tables. The statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) Version 22 software. Chi-square (X 2 ) and Z test were used to estimate the statistical significance, and a p-value of ˂0.05 was considered significant.Results:Out of 100 patients enrolled, 81 (81%) of them were aged <20 years and 19 (19%) belonged to the 20-25 years of age group. The majority (96%) of them were unmarried, and 77% of the participants were students pursuing a degree course. Most (88%) study participants belonged to the middle socioeconomic status. A vast majority (75%) believed that smoking is one of the risk factors for BC. The knowledge of the facts that late menopause (59%) and long-term usage of hormone replacement therapy (54%) could predispose to BC was moderate among the study participants. The presence of breast lumps (49%) and nipple discharge (27%) were considered warning signs of BC. The clinical breast examination (52%) and mammogram (41%) were considered the preferred methods for diagnosing BC. Based on the CHBMS, the average scores noted were susceptibility (2.18±1.01), seriousness (2.91±1.29), benefits (3.90±1.15), motivation levels (3.50±1.52), barrier levels (3.03±1.60), and self-efficacy, (1.87±1-32). The knowledge of the BC risk factors did not correlate with the CHBMS scores (p=0.1). However, the knowledge of BC warning signs and screening methods significantly correlated with CHBMS scores (p-0.006).Conclusions:The awareness regarding the risk factors for BC and the significance of breast self-examination practices in early detection were noticeably low among study participants.